Electoral Competence, Epistocracy, and Standpoint Epistemologies. A Reply to Brennan. - Lenczewska, Olga (International Journal of Philosophical Studies, 2021)
Jason Brennan's recent epistemic argument for epistocracy relies on the assumption that voter competence requires knowledge of economics and political science. He conjectures that people who would qualify as competent are mostly white, upper-middle- to upper-class, educated, employed men, who know better how to promote the interests of the disadvantaged than the disadvantaged themselves. My paper, first, shows that this account of voter competence is too narrow and, second, proposes a modified account of this concept. Brennan mistakenly reasons as though it is obvious that socially disadvantaged and oppressed people, by virtue of lacking sufficient knowledge of political science and economics, do not belong on an epistocratic council. This is because there is another way of being competent: possessing first-personal experience and knowledge unique to (and acquired through) disadvantaged or oppressed situatedness. Once voter competence is characterized accurately and more holistically, epistocracy's problematic implications of privileging already dominant genders, races, and classes, which characterize Brennan's account, no longer arise.